As consequências morais da epistemologia multicultural - Martini, Willian (2017)
This dissertation presents a discussion of multicultural epistemology, its implications, criticisms and possible consequences for a research and for our conceptions about morality. One author who became central to our work is Charles Taylor, not only for his specific contribution to multiculturalism, but also for his constant attack on the modern legacy that guides much of the thinking in contemporary philosophy. We examine disputes around the assertion that various factors are inherent in the culture and identity of individuals or groups with close ties to a way in which knowledge is produced and validated in different contexts. The critique of the generic subject's conception that has capacities (In a neutral way) to think of himself and the world around him, is the point that unites the epistemological approach of multiculturalists to Taylor's thinking within our work. However, there are many points of disagreement. The sociological aspect and the postmodern tendency of the production of some multiculturalists are characteristics in conflict with Taylor‘s conception of self and morality. We will also see that detractors of multicultural epistemology concentrate their arguments on a traditional ground of the study of knowledge - in which concepts such as "objectivity", "clarity", "rationality", for example, are not problematic. But the questions about the distinction between norm and value in this sense are not a clear point as is supposed. Undoubtedly, there are values within the practices and conceptions consolidated by modernity, as we will see throughout this work. Questions involving cultural context and the examination of the epistemological status of knowledge are in a rather thorny terrain, but we will weave our investigation resorting in several points to the study of Taylor‘s work. Nevertheless, we will also draw a division between multicultural epistemology and monocultural epistemology in order to throw some hypotheses about possible ways of understanding the moral consequences of openness to the "postulates" of multicultural epistemology.